2007
DOI: 10.1111/j.1399-0039.2006.763_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spontaneous abortions patients have more −14 bp/+14 bp heterozygotes in the 3′UT region of the HLA‐G gene in a Chinese Han population

Abstract: Although human leukocyte antigen (HLA)-G gene polymorphism is low, it may influence levels of protein expression and, in some cases, has been associated with pregnancy diseases. Apart from the 23 HLA-G alleles, including a null allele known as HLA-G*0105N, a 14-bp deletion or insertion in the 3'UT region also contributes to the HLA-G gene polymorphism. In order to discover any correlation between the 14-bp deletion polymorphism and pregnancy diseases, we isolated the genomic DNA from 24 recurrent spontaneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 16 publications
(24 reference statements)
3
35
1
7
Order By: Relevance
“…Проведенный анализ литературных данных показал, что аллель HLA-G 3'UTR 14-bp ins и со-ответствующий гомозиготный генотип достовер-но чаще встречается у женщин с ранними репро-дуктивными потерями [5,22,25]. Известно, что для HLA-генов всегда имеет место кодоминант-ная модель наследования, то есть постоянное участие в иммунных процессах всех унаследован-ных аллелей [15].…”
Section: Discussionunclassified
“…Проведенный анализ литературных данных показал, что аллель HLA-G 3'UTR 14-bp ins и со-ответствующий гомозиготный генотип достовер-но чаще встречается у женщин с ранними репро-дуктивными потерями [5,22,25]. Известно, что для HLA-генов всегда имеет место кодоминант-ная модель наследования, то есть постоянное участие в иммунных процессах всех унаследован-ных аллелей [15].…”
Section: Discussionunclassified
“…[81] Two other negative studies were published -one in 2010 that analyzed 143 RSA and 150 control couples in the Indian population [82] and another one in 2012 on an Iraqi population of 50 RSA and 50 control women. [83] By contrast, Xue et al discovered an excess of heterozygotes in Chinese RSA women, [84] while another more recent study from China indicated an increased number of +14 bp homozygotes in the RSA women. [85] Near the 14-bp Ins/Del, two polymorphisms (T1570VC and C1594A) were detected and found to be associated with RSA risk; [86] T1570C was in LD with the cases but not with the controls.…”
Section: "Wrong" Hla Programmingmentioning
confidence: 96%
“…Among these, 4 studies were excluded due to duplicate publications [32][33][34][35], three had incomplete data on allele and genotype frequency which we failed to get by emails to the corresponding authors [36][37][38], and an additional one was excluded due to the absence of a control group [39]. Consequently, the remaining 17 case-control studies which examined the association between the HLA-G 14-bp polymorphism and RM were finally included [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50][51] (Fig. 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Association between RM and HLA-G 14-bp insertion/deletion polymorphism allele Sixteen studies were included in assessing the association between HLA-G 14-bp insertion/deletion polymorphism allele and RM [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50]. As shown in Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%